Moderating Role of ESG Disclosure on Minority Shareholders and Tax Avoidance - Widiastutik, Rika Nur; Iqbal, Syaiful; Rusydi, Mohamad Khoiru (Journal of Accounting Research, Organization and Economics, 2024)
Objective - This study examined and analyzed the effect of minority shareholders on tax avoidance, which covers Environmental, Social, and Governance (ESG) disclosure as a moderating variable in manufacturing companies listed on the IDX for the 20182022. The minority shareholders consist of foreign ownership, institutional ownership, and managerial ownership.Design/Methodology - This study used secondary data taken from annual reports, sustainability reports, and the companys OSIRIS database. Moreover, a total of 254 research sample companies were selected for this study using a purposive sampling technique. In addition, this study used a quantitative method using panel data regression analysis.Results - This study discovered that the higher the foreign and managerial ownership, the lower the tax avoidance actions within the company, while institutional ownership has no effect on tax avoidance. Furthermore, the results of the moderation regression analysis showed ESG disclosures can strengthen the effect of foreign and managerial ownership on tax avoidance, but cannot moderate institutional ownership on tax avoidance.Research limitations/implications - As a solution to tax avoidance in Indonesia, OJK may take into account and strengthen ESG disclosures made by companies.Novelty/Originality - This study discussed tax avoidance actions in Indonesia based on company ownership, with a focus on minority shareholders. Additionally, ESG disclosure was investigated to determine whether it could affect the relationship between minority shareholders and tax avoidance.